Increasing Value and Protecting Business: Socialization of the Importance of Brands and Copyrights for Rice Traders in Kulon Progo Regency - Saputra, Viant Anggi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
This 2-day intensive community service program aims to improve the practical understanding of rice traders in Kulonprogo Regency about the importance of registered trademarks and copyrights in facing the challenges of rice counterfeiting, unfair competition, and legal vulnerabilities. Through participatory training methods (brand registration simulation, analysis of packaging copyright infringement cases, and focused discussions), 25-30 participants were invited to understand the strategic benefits of IPR: business protection, product differentiation, increased sales value, and prevention of legal risks. The results showed that 85% of participants experienced a significant increase in awareness, were able to identify the benefits of registered trademarks (such as quality assurance and the basis for lawsuits) and the risks of copyright infringement. As many as 60% of participants committed to taking concrete actions (brand registration consultation with DISPERDAG, review of packaging design). This program succeeded in laying the foundation for mindset transformation by providing practical guidance, booklets, and access to further assistance from DJKI/DISPERDAG, although ongoing support is needed to realize participants' commitments.